Replication kinetics of pathogenic Eurasian orthohantaviruses in human mesangial cells - Boegelein, Lukas; Schreiber, Pamela; Philipp, Alexandra; Nußhag, Christian; Eßbauer, Sandra; Zeier, Martin; Krautkrämer, Ellen (Virology journal, 2024)
Eurasian pathogenic orthohantaviruses cause hemorrhagic fever with renal syndrome (HFRS) characterized by acute kidney injury (AKI). The virulence of orthohantaviruses varies enormously and direct infection of different renal cell types contribute to pathogenesis. Glomerular mesangial cells play an essential role in the interplay between kidney cells and proper kidney function. Therefore, we analyzed the replication competence of different orthohantavirus species in primary mesangial cells and a mesangial cell line.
Online veröffentlicht: 1. Oktober 2024
Gesehen am 04.03.2025